The difference in the measurement of freeway space in an upright sitting position with and without electromyograph - Halim, Stevani Monika; Sumarsongko, Taufik; Adenan, Aprilia (Universitas Padjadjaran, 2015)
Introduction: Measurement of vertical dimension is very important because improper measurement of vertical dimension may create stomatognatic problem. Electromyography is a tool for recording electrical signals generated from the mechanism of muscle contraction.This study aims to determine the accuracy of measurements of FWS with and without electromyograph. Methods: This research was a descriptive comparative study using purposive sampling methods. Measurements of FWS in an upright sitting position with and without electromyograph were done on 10 students of class 2008 from Faculty of Dentistry, UNPAD who met the criteria. Data were analyzed by t test statistics, showed that there were significant differences in the measurements with and without electromyography in upright sitting position. Results: The mean of FWS measured with electromyography was 2.38 mm with standard deviation of 0.44 mm, whereas the mean of FWS measured without electromyography was 1.69 mm with a standard deviation of 0.46 mm. Average FWS in men measured with electromyography was 2.51 mm with a standard deviation of 0.15 mm, whereas the mean without electromyography was 1.68 mm with a standard deviation of 0.43 mm. Average FWS in women measured with electromyography was 2.35 mm with a standard deviation of 0.49 mm, whereas the mean without electromyography was 1.69 mm with a standard deviation of 0.50 mm. Conclusion: The measurements of FWS with electromyograph in an upright seating position was greater than without electromyography.